Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Course Review Horay Pada Kelas IV SDN 01 Benteng Pasar Atas - Muhammad Siddiq; Reinita Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research generally aims to improve learning outcomes in social studies learning by using the Cooperative Learning model Course Review Horay type in class IV SDN 01 Benteng Pasar Atas Bukittinggi. This research is a classroom action research using qualitative and quantitative approaches. In the implementation, this research consists of two cycles, namely cycle I two meetings and cycle II one meeting. Includes four stages, namely planning, implementation, observation and reflection. The subjects of this study were 36 teachers and grade IV students. The results showed an increase in the RPP in the first cycle was 72.77% with good qualifications increased in the second cycle to 97.22% with very good qualifications. Assessment of the implementation of learning in the aspects of the first cycle of teachers was 78.36% with good qualifications increased in the second cycle to 97.22% with very good qualifications, and from the aspects of the first cycle students was 73.88% with good qualifications increasing in the second cycle to 94 , 44% with very good qualifications